2018
DOI: 10.1007/s00330-017-5190-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of 18F-fluorocholine PET imaging in parathyroid surgery

Abstract: • With F-fluorocholine PET imaging, parathyroid adenomas could be detected in 96.2%. • F-fluorocholine imaging is a highly accurate method to detect parathyroid adenomas. • We encourage its use, where ultrasound fails to detect an adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 27 publications
0
48
0
2
Order By: Relevance
“…Only Rep et al [25] reported scanning patients 3 times, at 5, 60 and 120 min after FCH injection. The FCH dosage was fixed in 16 studies, in the range of 100-230 MBq [15,[19][20][21][22][23][24][25][26][27][28][31][32][33][34]; it was adjusted to the patient's body weight in 5 (1.5-3.2 MBq/kg) and not declared in two studies [12,16,17,29,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Rep et al [25] reported scanning patients 3 times, at 5, 60 and 120 min after FCH injection. The FCH dosage was fixed in 16 studies, in the range of 100-230 MBq [15,[19][20][21][22][23][24][25][26][27][28][31][32][33][34]; it was adjusted to the patient's body weight in 5 (1.5-3.2 MBq/kg) and not declared in two studies [12,16,17,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons between FCH PET/CT and 99mTc-MIBI SPET/CT with a dual-phase and/or subtraction protocol were reported in numerous studies (Table 2; [4,[12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]).…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear medicine option with superior spatial resolution and sensitivity is 18 F-Fluorocholine PET/CT. 18 F-Fluorocholine (FCH) is marker of cell membrane turnover (19). Sensitivity of 94%, specificity 96%, PPV 90.2%, NPV 97.4% and diagnostic accuracy 95.3% were achieved using this tracer, making it the most promising tracer with high diagnostic performance (10,20).…”
Section: Discussionmentioning
confidence: 99%
“…Following incidental detection of FCH uptake in parathyroid adenoma, several clinical studies have been published on the role of FCH PET/CT in hyperparathyroidism, and they have shown better diagnostic performance of FCH PET/CT in comparison with other conventional imaging methods, with higher sensitivity and equally high specificity (7)(8)(9)(10)(11)(12)(14)(15)(16)(17). A recent meta-analysis evaluating the diagnostic performance of FCH PET/CT in hyperparathyroidism revealed that the sensitivity and specificity of FCH PET/CT were 90% and 94%, respectively (18), and another study also reported excellent sensitivity, PPV, and detection rate of 95%, 97%, and 91%, respectively (19).…”
Section: Discussionmentioning
confidence: 99%